Seroprevalence and risk factors associated with bovine Leukemia virus infection in argentine beef cattle - Porta, Natalia Gabriela; Suarez Archilla, Guillermo; Miotti, Camila; Molineri, Ana Ines; Alvarez, Irene; Trono, Karina Gabriela; Signorini Porchiett, Marcelo Lisandro; Ruiz, Vanesa (Elsevier, 2023)
Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis, an endemic disease in dairy cattle of Argentina. However, little is known about the seroprevalence of BLV in beef cattle. In this study, we conducted a cross-sectional study including farms from thirteen provinces of Argentina. A total of 5827 bovine serum samples were collected from 76 farms and analyzed using an in-house developed enzyme-linked immunosorbent assay. Information about herd management was collected through a questionnaire, and univariate and multivariate analyses were performed to detect risk factors associated with BLV infection. Herd-level seroprevalence was 71.05%, while the mean animal-level seroprevalence was 7.23% (median = 2.69%; min = 0, max = 75). Only two provinces had no positive BLV samples. The other eleven provinces showed more than 50% of their farms infected with BLV. The multivariate model revealed that BLV prevalence was significantly associated with the use of animals raised in the same farm for cattle replacement (P = 0.005), breeding cows by natural mating with a bull (P < 0.001), and weaning calves after 6 months of age (P = 0.011). This extensive study revealed that BLV seroprevalence in Argentine beef farms has increased during the last years and allowed identifying some management practices associated with BLV prevalence. These data deserve special attention because BLV infection in beef cattle seems to lead to a dissemination pattern similar to that observed during the last decades in dairy cattle, especially considering that Argentina is the sixth beef producer in the world, with about 5% of global beef production.